High density planting in rubber plantations: Effect on growth and yield - Philip, Annie; Lakshmanan, Radha; Jessy, M.D.; Varghese, Mary (Journal of Plantation Crops, 2014)
Planting density is an important parameter influencing the growth and yield of trees. A field study was conducted at Central Experiment Station of Rubber Research Institute of India, Chethackal, Kerala with clone RRII 105 in split plot design with five densities as main plot treatments and two fertilizer quantities as sub plot treatment replicated four times to study the effect of density of planting on growth and yield of rubber. The five densities tested are 420 trees ha-1 (4.9 m x 4.9 m), 479 trees ha-1 (4.6 m x 4.6 m), 549 trees ha-1 (4.3 m x4.3 m), 638 trees ha-1 (4 m x 4 m) and 749 trees ha-1 (3.7 m x 3.7 m) and the two subplot treatments are recommended dose of fertilizer (RDF) on unit area basis and RDF on per plant basis. Growth of the plants was not significantly influenced by the different planting densities up to eighth year after planting, but in the later years increased planting density decreased the girth and trees in the lowest density of 420 trees ha-1 recorded significantly higher girth. The lowest density also recorded significantly higher per tree yield. However, the annual yield per hectare was the highest (2553 kg) in the highest density of 749 trees ha-1 which was comparable (2457 kg) with that of the density of 549 trees ha-1. Bole height increased with planting density. But the bole volume, 18 years after planting was not significantly influenced by the planting density. Bark thickness was the highest (9.76 mm) in the lowest density and it was comparable (9.40) with that of the density 549 trees ha-1. Effect of fertilizer application on per plant basis and area basis was not significant throughout the study period. Based on 7 years yield data highest BCR of 3.16 and IRR of 29.11 per cent were obtained for the density of 549 trees ha-1.